Evaluation of The Effectiveness of Rotational Conjunctival Flap Compared to Bare Sclera with Mitomycin C After Surgical Removal of Primary Pterygium - Amin, Akhtar; Ahmad, Ambreen; Iqbal, Arshad; Khan, Sher Akbar (Indus Journal of Bioscience Research, 2025)
Background: Primary pterygium is a common ocular condition requiring effective surgical management to minimize recurrence. While mitomycin C is frequently used as an adjunct in pterygium surgery, rotational conjunctival flap offers an anatomical restoration approach. Their comparative efficacy remains a subject of investigation. Objective: To compare the efficacy of rotational conjunctival flap and mitomycin C after surgical removal of primary pterygium. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from February 2024 to January 2025 at the Department of Ophthalmology, Saidu Group of Teaching Hospital, Swat. Methodology: A total of 196 patients with primary pterygium, aged 18–60 years, were randomized into two equal groups. Group A underwent rotational conjunctival flap surgery, while Group B received 0.04% MMC application during surgery. Exclusion criteria included systemic diseases, recurrent pterygium, and corneal pathologies. Surgical outcomes were assessed over six months, with efficacy defined as the absence of fibrovascular regrowth ≥1 mm beyond the limbus. Results: Group A demonstrated significantly higher efficacy (90.8%) compared to Group B (76.5%, p=0.007). Stratified analysis revealed superior outcomes for rotational conjunctival flap across various subgroups, including patients >45 years, males, right-eye involvement, and pterygium duration >18 months. Both techniques were well tolerated, with no major complications reported. Conclusion: Rotational conjunctival flap surgery is significantly more effective than mitomycin C in preventing recurrence of primary pterygium.